Coprocessing of a Turkish lignite with a cellulosic waste material - 1. The effect of coprocessing on liquefaction yields at different reaction temperatures - Karaca, F; Bolat, E (ELSEVIER SCIENCE BV, 2000)
In recent years, the liquefaction potential of waste materials has been investigated to increase the yield of coal conversion processes and the quality of liquid fuels from coal. The results have shown that the coprocessing of coal with biowaste materials increases liquefaction yields. In this study, the effects of liquefaction of Soma lignite with sawdust as a coprocessing agent, on total conversion, oil + gas total yields, asphaltene yields and preasphaltene yields were investigated at five different temperatures, 300, 325, 350, 375 and 400 degrees C, 40 atm initial cold pressure, 1/1 (wt/wt) sawdust/lignite ratio and 3/1 (vol/wt) tetralin/(lignite + sawdust) ratio values. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: lignite; sawdust; liquefaction; coprocessing; COAL; COLIQUEFACTION; Chemistry; Energy & Fuels; Engineering